세대 간 및 국가 간 차이에 따른 신제품 수용태도에 대한 실증 연구 -한국과 중국 소비자를 중심으로 - 서용모; 김형준; Seo, Yong-Mo; Kim, Hyung-Jun (한국콘텐츠학회 논문지, 11(10), 2011)
The primary purpose of this paper is to identify the influencing factors on the new products adoption between countries and generations. For this purpose, a research is developed based on the relevant literature reviews. Data have been collected from 524 persons and were tested by t-test and various statistical methods. The results of this empirical study are summarized as follows. In the cultural factors, the groupism has high discretion in China old generation. The materialism and shopping preference have high discretion in two young generations. There is no difference between the two groups in the distance of power. In innovativeness of personality, Korea and China young generation have high discretion. Innovativeness has high discretion in Korea and China youngs. Cognition and sensory innovativeness are has low discretion in Korea old. In the social risk perception, physiological, functional general and financial risk has high discretion in China old. In risk reducing behavior, the normative taking level and ad, new product adoption has high discretion in Korea and China youngs. But, the influence of others has high discretion in China old generation. The safety and brand reputation are no influences. The findings have a several marketing strategies in generation and countries. 본 연구는 신제품 수용에 있어서 국가별 및 세대별 차이에 영향을 미치는 요인을 구체화시키는데 주목적이 있다. 연구의 목적을 달성하기 위하여 관련된 선행연구의 고찰을 통해 한국과 중국의 소비자들을 대상으로 신제품의 수용태도에 대해 524명을 대상으로 t-test를 통해 실증검증을 실시하였다. 본 연구의 결과를 요약해보면 문화적 요인에서의 집단주의 항목에서는 중국의 구세대에서 높게 나타났으며, 권력격차 항목에서는 집단 간 인식의 차이가 없는 것으로 조사되었다. 물질주의와 쇼핑선호 성향에 대해서는 각국의 젊은 세대들이 구세대보다 높은 것으로 나타났다. 개인의 혁신성에 대한 요인에서는 각국의 구세대들이 젊은 세대들보다 더 높게 나타났으며, 혁신성향은 각국의 젊은 세대들이 구세대들 보다 혁신성향이 높은 것으로 나타났다. 인지혁신과 감각혁신은 한국의 구세대가 낮은 혁신성향을 나타났다. 지각된 위험요인에 대한내용으로 심리적요인, 기능위험인식, 전반적인 위험인식 및 재무위험인식요인에 대해 높게 나타났으며 사회위험인식 요인은 중국의 구세대가 다른 집단에 비해 낮게 나타났다. 위험감소행동요인에 대해서는 규범적 수용정도, 광고의 영향, 신제품 수용에 대한 요인은 각국의 젊은 세대가 높게 나타났고, 반면에 프리미엄 지불에 대한 요인으로는 각국의 구세대들이 인식이 높게 나타났으며, 타인의 영향은 중국의 구세대에서 가장 높게 나타났다. 또한 안심확인과 브랜드 명성은 집단 간 차이가 없는 것으로 나타났다. 본 연구의 결과를 토대로 지역과 세대를 고려한 마케팅 전략을 제시하는 시장세분화 전략을 통해 신제품의 수용을 강화 시킬 수 있을 것이다.